Hubungan Tingkat Pendidikan Dan Pengetahuan Ibu Hamil Dengan Keteraturan Pemeriksaan Kehamilan Di Wilayah Kerja Puskesmas Sindang Jati Tahun 2024 - Sembiring, Agnes Kresensia; Putri, Yesi; Ayu Lestari Nurjana, Nimas (Jurnal Kesehatan Mitra Sekawan, 2025)
The current maternal mortality rate (MMR) is still far from the Sustainable Development Goals (SDGs) target of 70 per 100,000 live births by 2030. Based on the results of the Indonesian Demographic Health survey in 2023, it shows a significant increase in MMR, which is 359 pe 100,000 live births (SDKI, 2024). Antenatal care is a health service provided periodically by health professionals to improve the health status of pregnant women and their fetuses. The purpose of the study was to determine the relationship between the level of education and knowledge of pregnant women with the regularity of pregnancy checks in the working area of the Sindang Jati Health Center in 2024. This study uses analytic research with cross sectional design. The population used by pregnant women in the work area of Sindang Jati Health Center in June-July 2024 was 40 pregnant women. The sampling technique used total sampling technique. Chi-square test results show that the variable level of education of pregnant women with regularity of pregnancy checks obtained chi-square p-value 0.001 (α <0.05), the level of education of pregnant women with regularity of pregnancy checks obtained chi-square p-value 0.001 (α <0.05), so it can be concluded that the relationship between the level of education and knowledge of pregnant women with regularity of pregnancy checks in the working area of Sindang Jati Health Center in 2024. It is recommended to increase the knowledge of the importance of regular pregnancy checks to detect the health of pregnant women.